Daya Hambat Hidrolisis Karbohidrat Oleh Ekstrak Daun Murbei - S. Syahrir; Komang G Wiryawan; Aminuddin Parakkasi; Winugroho Winugroho; W. Ramdania (Jurnal Agripet, 2009)
Inhibition hydrolysis of carbohydrate by mulberry leaves extractABSTRACT. Mulberry leaves has a great potential as animal feeds because of its high nutrient content, but has deoxynojirimycin (DNJ) active matter. It is potential to inhibit carbohydrate hydrolysis process, come to monosaccharides. The objective of this experiment is to study the inhibiting ability of mulberry leave extract in carbohydrate hydrolysis process. The kinds of carbohydrates were using glucose, maltose, sucrose and starch. This experiment used twenty four of 60 days old male mice (Mus musculus). Diet and water were given ad libitum. Treatment were allocated ina factorial completely randomized design with three replications and two factors containing of completely mulberry leaves extract and variance of carbohydrates. Variable observed were feed consumtion, feed digestibility, body weight gain and blood glucose. The data were analyzed with univariate analysis of variance. The result showed that inclusion of mulberry leaves extract had decrease body weight (P 0,05) and reduce blood glucose (P 0,05).